2021
DOI: 10.3390/app11156770
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Path Planning Method Based on Q-Learning and Neural Network for Robot Arm

Abstract: Path planning for robot arms to reach a target and avoid obstacles has had a crucial role in manufacturing automation. Although many path planning algorithms, including RRT, APF, PRM, and RL-based, have been presented, they have many problems: a time-consuming process, high computational costs, slowness, non-optimal paths, irregular paths, failure to find a path, and complexity. Scholars have tried to address some of these issues. However, those methods still suffer from slowness and complexity. In order to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…We tested this computer vision-based path planning algorithm through simulation and experimental methods. The results revealed that this research overcame the limitations of our previous research [9].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We tested this computer vision-based path planning algorithm through simulation and experimental methods. The results revealed that this research overcame the limitations of our previous research [9].…”
Section: Discussionmentioning
confidence: 65%
“…To this end, first, we compare our method with other methods in terms of speed which is a crucial feature in real-time path planning. To compare this method with other path planning methods, we refer to our previous study [9]. In that paper, we compared the speed of running time in our hybrid path planning method and other conventional path planning methods such as RL-based, APF, PRM, and RRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that the link of the robot arm makes a kinematic chain and the end of this chain is termed an end effector to execute the normal operations, like, cutting, grasping, and so forth. The robot arm is mostly applied in current society (Soria et al, 2019; Abdi et al, 2021), and also it is applied in industrial manufacturing to perform operations, like, welding, assembly, spraying, and so forth. Besides, it is applied as a surgical aid in the medical domain (Misra & Singh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…After setting a reward mechanism, with the Q-learning, robot can find an optimal path which obtains the max rewards among all, staring from the current state. On the one hand, for solitary robots, Q-learning combined with neural network present a new hybrid path planning method for robot arm [5]. Besides, using Q-learning helps high-level path planning for an autonomous sailboat robot [6].…”
Section: Introductionmentioning
confidence: 99%